2017
DOI: 10.1590/1678-457x.32516
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the physicochemical profiles of buriti from the Brazilian Cerrado and the Amazon region

Abstract: Demand for native fruits has been expanding, due to the increasing interest in foods with possible health benefits. The buriti (Mauritia flexuosa L. f.) is a native Brazilian fruit, appreciated by local populations, and its products are already on the market. This study investigated the physical characteristics and nutritional composition of buriti pulp, obtained from typical Cerrado and Amazon regions in Brazil. These regions influenced physical parameters and chemical composition. The fruits originating in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 26 publications
2
20
3
4
Order By: Relevance
“…The mass of the pulp varied from 9.57 to 19.56 g, with a yield of 22.7%. Another study found a lower mass value than the present study (ranging from 3.00 to 7.48 g) (Cândido & Silva, 2017). The yield found in the present study was different from related studies by other researchers of buriti fruit from the Brazilian Cerrado.…”
Section: Physical and Physicochemical Characterizationcontrasting
confidence: 99%
See 4 more Smart Citations
“…The mass of the pulp varied from 9.57 to 19.56 g, with a yield of 22.7%. Another study found a lower mass value than the present study (ranging from 3.00 to 7.48 g) (Cândido & Silva, 2017). The yield found in the present study was different from related studies by other researchers of buriti fruit from the Brazilian Cerrado.…”
Section: Physical and Physicochemical Characterizationcontrasting
confidence: 99%
“…The moisture concentration was similar to that observed by Schiassi et al (2018), in fruits of area of the São Paulo state, Brazil and also observed by Cândido & Silva (2017). Regarding the fiber content, this was higher than 6.02 g.100 g -1 reported by Schiassi et al (2018) and higher than 6.69 observed in another study (Cândido & Silva, 2017).…”
Section: Physical and Physicochemical Characterizationsupporting
confidence: 87%
See 3 more Smart Citations